The prediction of disempowering motivational climate on burnout among youth badminton players: The mediating effects of basic psychological needs - Tsai, Y. T.; Chi, L. K. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Athletes` burnout has been an important issue which results in dropout the sport. The present study aimed to examine whether the impact of coach`s disempowering motivational climate on burnout is mediated by basic psychological needs among youth badminton players. Methods: One hundred and fifty-two high school badminton players (males=85, females=67, Mage=16.55) were recruited to this study. Participants were asked to complete questionnaires which include Disempowering Motivational Climate Questionnaire (Appleton, Ntoumanis, Quested, Viladrich, Duda, 2015), Basic Need Satisfaction Scale (Deci, Ryan, Gagné& Kornazheva, 2001), and Athlete Burnout Questionnaire (Raedeke, & Smith, 2001). Results: Results showed that disempowering motivation climate positively predicted exercise burnout (R²=21%). =21%). Disempowering motivational climate negatively predicted relatedness, competence, and autonomy. The explained variances were 18%, 6.1% and 3.5% respectively. In addition, in terms of the mediating effect of basic psychological needs, the prediction of disempowering motivational climate on burnout was only mediated by competence but not relatedness and autonomy. Discussion: In accord to the previous studies regarding the relationships between motivational climates and burnout (Kang, 2004; Wang, 2008), disempowering motivational climate negatively predicted burnout. Moreover, one of the basic needs - competence played as a mediator. In other words, disempowering motivational climate negatively influence youth badminton players` competence and then negatively predicted their burnout. According to these results, coaches should avoid creating disempowering motivational climate to protect athletes` competence and then reduce the tendency of the burnout. ABSTRACT FROM AUTHOR